Landscape and landform potential for the development of small-scale wineries: scientific methodology for a geographical definition of specific terroirs. The case study of the rural commune of Hażlach in Poland - Buława, Bartłomiej; Antonowicz, Laura; Cheluszka, Karol; Dylong, Karolina; Torres, Ignacio Fernandez (Bulletin of Geography. Socio-economic Series, 2025)
The research contextualizes the emergence of viticulture in non-traditional vine regions due to climate change and examines the landscape potential for such development on the sample of Hażlach commune in Poland. The research problem addressed is how areas with specific landscape characteristics favourable to viticulture but not constrained by historical or industrial-scale wine traditions, possess a greater capacity to develop sustainable and identity-driven wine production models. These conditions are particularly conducive to fostering a unique terroir and supporting rural development based on cultural heritage. The methodology employs GIS-based terrain analysis, utilizing slope, exposure, and proximity to water bodies, to identify optimal zones for viticulture. 11% of the commune meets the criteria for site-specific terroir development. The research highlights the potential of small-scale vineyard and oenotourism in Hażlach not only to establish a distinctive wine culture but also to contribute to the restoration of the landscape of small farmstead structures.